Mutant Mungbean Lines from Radiation and Chemical Induction - Wongpiyasatid, Arunee; Chotechuen, Somsong; Hormchan, Praparat; Ngampongsai, Sumana; Lamseejan, Siranut; Pichitporn, Somyot (Agriculture and Natural Resources, 1998)
Gamma rays of 500 Gy and the chemical mutagen, 1% ethylmethane sulphonate (EMS) were administered to induce mutation in mungbean KPS 1 and CN 36 varieties for improvement of disease resistance to cercospora leaf spot and powdery mildew as well as producing high yields. The individual plant and plant-row selections were made in M2 and M3 and in M3 and M4 of KPS 1 and CN 36 respectively. The selected characters observed were the low level of powdery mildew, pods protruding up above the canopy, early maturity, and purple-red petioles. Preliminary yield test of 27 selected lines comparing to original varieties, KPS 1 and CN 36, revealed potentiality of some lines that might be developed into good varieties. These were, M5-8 with good pod setting, M5-19 with pods protruding up above the canopy, M5-21 and M5-22 with good plant type and high pod setting, and M5-24 with early flowering. All five mutant lines possessed moderate resistance to powdery mildew as did KPS 1, while CN 36 moderate susceptibility. The controls as well as the selected lines were also moderately resistant to cercospora leaf spot. For further investigation, artificial inoculation of the pathogens in severe infection would be made in yield test so that only most resistant lines could be chosen.